Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Innovation technologique et pratiques domestiques : analyse d'une expérience domotique - Beillan, Véronique (Sociétés contemporaines, 1994)
À partir du suivi sociologique d'une expérience domotique portant sur quinze logements du secteur HLM, cette étude traite des conditions d'appropriation sociale d'une nouvelle technologie domestique. Après un exposé de la méthode de recueil des données, basée sur la réalisation de trois vagues ď entretiens - réparties sur trois ans - auprès des ménages du lotissement domotique, l'article présente les premiers résultats ainsi que les nouvelles pistes de recherche à approfondir lors de la troisième et dernière phase du suivi. L'analyse comparative des deux premières vagues d'entretiens a permis de noter la permanence des attentes et des attitudes des ménages à l'égard de la domotique mais aussi le caractère hétérogène et ambivalent de ces dernières. Des freins ď ordre socio-économique et socio-culturel à l'intégration sociale de la technique ont été identifiés. Ainsi, des liens se dessinent entre l'automatisation des tâches et certains éléments tels que le statut et l'identité de la femme, l'organisation et la hiérarchisation des activités domestiques, les pratiques de délégation et ď externalisation du travail domestique.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; care; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Nomadic subjects: Embodiment and sexual difference in contemporary feminist theory - Braidotti, Rosi (Columbia University Press, 1994)
Nomadic Subjects plaide pour un nouveau type de pensée philosophique, qui inclurait les idées du féminisme et abandonnerait le mode hégémonique qui est conventionnellement adopté dans la haute théorie. La prose personnelle, surprenante et vivante de Braidotti insiste sur une intégration du féminisme dans le discours dominant. Les essais explorent les problèmes qui sont au cœur des débats féministes actuels, y compris la relation de l'épistémologie occidentale à la «question de la femme», le féminisme et l'éthique biomédicale, le féminisme européen et la façon dont les féministes américaines pourraient se rapporter aux mouvements européens.
Keywords: LGBTQIA2+; cours; discipline; europe; fem1000; genre; har4600; identités LGBTQIA2+; philosophie politique; post-structuralisme; premier cycle; régions géographiques; sciences humaines; soc2014; thématiques; épistémologie

La mise en forme des pratiques domestiques dans le travail de conception d'appareils électroménagers - Chabaud-Rychter, Danielle (Sociétés contemporaines, 1994)
Ce texte a pour objet les relations que les concepteurs d'appareils électroménagers établissent avec les pratiques domestiques au cours de leur travail. Il traite de la mise en forme des pratiques culinaires des femmes opérée par l'innovateur pour leur transmutation en opérations mécaniques d'appareils de cuisine. Divers processus par lesquels l'expérience pratique domestique est traduite pour être rendue lisible et façonnable dans le monde industriel sont ainsi mis en évidence. Puis on tente de montrer comment les activités domestiques sont prises en compte et reconfigurées dans le travail que fait l'innovateur sur les propriétés et les dispositifs des appareils offerts à la perception, à la réflexion et à la manipulation au cours de l'usage.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; care; cours; discipline; europe; france; patriarcat; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Feminism and postmodernism - Ferguson, Margaret; Wicke, Jennifer (Duke University Press, 1994)
This collection of essays explores the significant agreements and tensions between contemporary feminist and postmodern theories and practices. Having brought enormous changes to conceptions of the body, identity, and the media, postmodernity compels the rethinking of many feminist categories, including female experience, the self, and the notion that "the personal is political." Feminist analysis has been equally important, though not always equally acknowledged, as a force within postmodernism. Feminist writings on subjectivity, master narratives, and the socioeconomic underpinnings of the master narrative of theory itself have been particularly influential. This volume traces the crossings and mutual interrogations of these two traditions into the arenas of cultural production, legal discourse, and philosophical thought. Multidisciplinary and international in their collective focus, the essays range from a study of Madonna as an Italian American woman who is revising the cultural meanings of an ethnic feminism to a unique interview with Mairead Keane, the national head of the Women’s Department of the Irish political party Sinn Fein. Turning the prism of postmodern feminism onto such diverse cultural objects as literary and literary critical texts, contemporary film, and music, these essays intervene in debates regarding technology, sexuality, and politics. Challenging modern feminisms to articulate their inescapable relation to postmodern society, this expanded edition of a special issue of boundary 2 also explores ways in which feminism can work as the cutting edge of a global postmodernism. Contributors. Salwa Bakr, Claire Detels, Margaret Ferguson, Carla Freccero, Marjorie Garber, Barbara Harlow, Laura E. Lyons, Anne McClintock, Toril Moi, Linda Nicholson, Mary Poovey, Andrew Ross, David Simpson, Kathyrn Bond Stockton, Jennifer Wicke
Keywords: amériques; approches et analyses; cours; discipline; fem1000; féminisme pop; irlande; philosophie; postmodernisme; premier cycle; régions géographiques; sciences humaines; troisième vague; états-unis; études culturelles

Volatile bodies: toward a corporeal feminism - Grosz, E. A. (Theories of representation and difference, 1994)
Volatile Bodies demonstrates that the sexually specific body is socially constructed: biology or nature is not opposed to or in conflict with culture. Human biology is inherently social and has no pure or natural "origin" outside of culture. Being the raw material of social and cultural organization, it is "incomplete" and thus subject to the endless rewriting and social inscription that constitute all sign systems. Examining the theories of Freud, Lacan, Merleau-Ponty, Foucault, Deleuze, Derrida, etc. on the subject of the body, Elizabeth Grosz concludes that the body they theorize is male. These thinkers are not providing an account of "human" corporeality but of male corporeality. Grosz then turns to corporeal experiences unique to women--menstruation, pregnancy, childbirth, lactation, menopause. Her examination of female experience lays the groundwork for developing theories of sexed corporeality rather than merely rectifying flawed models of male theorists.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; lit4700; premier cycle; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; théories féministes

L'énigme de la femme : la femme dans les textes de Freud - Kofman, Sarah (Librairie générale française, 1994)
Freud devant l'énigme de la femme. Ombres et mystères. Questions et suggestions. A partir d'une minutieuse exploration de l'ensemble des textes freudiens, Sarah Kofman souligne les ambiguïtés du fondateur de la psychanalyse quand il aborde le problème de la féminité. Et notamment l'étrangeté de son attitude, faite d'atermoiements et de résistances, où l'embarras et l'inquiétude semblent finalement l'emporter sur l'esprit de rigueur dont il se réclamait. Au bout du compte, explique Sarah Kofman, les réponses données par Freud relèvent de la spéculation. Plus que des réponses, même, ce sont des solutions-écran qui servent de couverture à ce qui ne saurait être regardé en face : le sexe de la femme, de la mère. La fameuse envie du pénis, cette " idée fixe " de Freud, est l'une des pseudo-solutions, destinée à fixer la femme dans une position immuable, à maîtriser son caractère, son instabilité, sa mobilité qui la rendent inaccessible, effrayante, énigmatique : " criminelle " aux yeux des hommes. L'Enigme de la femme ou la psychanalyse revisitée.
Keywords: 1900-1999; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; patriarcat; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; systèmes d'oppressions

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques